2018
DOI: 10.2478/jamsi-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Air passengers forecasting for Australian airline based on hybrid rough set approach

Abstract: Accurate and reliable air passenger demand is very important for policy-making and planning by tourism management as well as by airline authorities. Therefore, this article proposed a novel hybrid method based on rough set theory (RST) to construct decision rules for long-term forecasting of air passengers. Level (mean) and trend components are first estimated from the air passengers time series data using DES model in the formulation of the proposed hybrid method. Then the rough set theory is employed to comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…They indicated that 2 years single moving average is closer to the original data than the exponential smoothing method. The study by Sharma et al (2018) forecasted air passengers by using an exponential smoothing method. However, there are studies in the field, which used traditional multiple regression to modern machine learning techniques for time series forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They indicated that 2 years single moving average is closer to the original data than the exponential smoothing method. The study by Sharma et al (2018) forecasted air passengers by using an exponential smoothing method. However, there are studies in the field, which used traditional multiple regression to modern machine learning techniques for time series forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rough set is used in data analysis to discover basic patterns in data, eliminate redundancies, and develop decision rules. Sharma et al (2018Sharma et al ( , 2021Sharma et al ( , 2022 developed various hybrid methods using rough set theory to create decision rules useful for realworld problems. Several scholars are working on this concept, which is being applied to a variety of fields such as in (Greco et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A concept of the Rough Fuzzy set model for a set-valued ordered fuzzy decision system was presented (Bao et al, 2014). In order to create decision rules for long-term forecasting of air passengers suggested a novel hybrid method based on rough set theory (Sharma et al, 2018). Then they used a combination technique to evaluate India's sugarcane production based on the rough set approach (Sharma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%